Interaction between serum cotinine and body mass index on asthma in the children: a cross-sectional study - Li He; Xiaojing Xi (BMC, 2022)
Abstract Background The purpose of this study was to explore the interaction between serum cotinine (a marker of environmental tobacco smoke exposure) and body mass index (BMI) on asthma in children. Methods This cross-sectional study relied on representative samples of American children included in the National Health and Nutrition Examination Survey in 1999-2018. Multivariate logistic regression analyses were to evaluate the association between serum cotinine level, BMI z-score and asthma. Serum cotinine was dichotomized at 0.0436 ng/mL. Interactions were examined by the estimated joint effect of BMI and serum cotinine levels. We also performed interaction analyses in age and ethnicity subgroups. Results Among the 11,504 children aged 3 to 12 years included in the analysis, 15.86% (n = 1852) had childhood asthma, 15.68% (n = 1837) were overweight, and 17.31% (n = 2258) were obese. Compared to low serum cotinine, high serum cotinine was significantly associated with asthma [odds ratio (OR) = 1.190, 95% confidence interval (CI): 1.004-1.410]. Overweight (OR = 1.275, 95%CI: 1.079-1.506) and obesity (OR = 1.636, 95%CI: 1.354-1.977) were significantly associated with asthma compared with normal weight. The adjusted attributable proportion of interaction = 0.206 (95%CI: 0.075-0.337) and the adjusted synergy index = 1.617 (95%CI: 1.126-2.098) indicated that there was a significant synergistic effect of serum cotinine levels and BMI on asthma. In males, females, non-Hispanic White and other Hispanic, there were synergistic interactions between serum cotinine levels and BMI on asthma. Conclusion A synergistic interaction between serum cotinine and overweight/obesity on childhood asthma was found. For children with asthma, both intensive weight interventions in overweight or obese children and intensive passive smoking interventions in children exposed to the environment may be important.